2021
DOI: 10.33594/000000398
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of IL-2 and TRAIL Proteins Expressed by Recombinant Salmonella in Murine Bladder Cancer Cells

Abstract: Background/Aims: Cancer is the second most deadly disease in the world. The bladder cancer is one of the most aggressive types and shows a continuous increase in the number of cases. The use of bacteria as live vectors to deliver molecules directly to the tumor is a promising tool and has been used as an adjuvant treatment against several types of cancer. The aim of this study was to investigate the antitumor effect of Interleukin 2 (IL-2), TNF-related apoptosis-inducing ligand (TRAIL) and protein MIX against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Subsequently, three major signaling pathways, including PI3K-AKT, JAK-STAT, and MAPK/ERK are activated [ 149 ] to mediate cell growth, survival, and differentiation, and cytokine production (IL-4, IL-6, IL-12) [ 150 , 151 ]. Thus, in breast cancer [ 389 ], IL-2 plays an anti-tumor effect [ 390 ] due to increased recruitment of IL-2-releasing NK cells and the induction of anti-apoptotic function in CD8 + T cells [ 391 ], the main effector of the antitumor response [ 392 ]. IL-2 can promote activation and proliferation of CD8 + T cells in early tumor stage but can deplete CD8 + T cells in late tumor stage [ 393 ] ( Figure 1 ).…”
Section: Interleukin-2 (Il-2)mentioning
confidence: 99%
“…Subsequently, three major signaling pathways, including PI3K-AKT, JAK-STAT, and MAPK/ERK are activated [ 149 ] to mediate cell growth, survival, and differentiation, and cytokine production (IL-4, IL-6, IL-12) [ 150 , 151 ]. Thus, in breast cancer [ 389 ], IL-2 plays an anti-tumor effect [ 390 ] due to increased recruitment of IL-2-releasing NK cells and the induction of anti-apoptotic function in CD8 + T cells [ 391 ], the main effector of the antitumor response [ 392 ]. IL-2 can promote activation and proliferation of CD8 + T cells in early tumor stage but can deplete CD8 + T cells in late tumor stage [ 393 ] ( Figure 1 ).…”
Section: Interleukin-2 (Il-2)mentioning
confidence: 99%
“…The researchers inserted IL-2 or/and TRAIL genes into the genome of attenuated Salmonella strain SL3261 and examined the effect of this Salmonella strain on BC in mice. The recombinant SL3261 strain caused cell membrane damage, increased NO production, and promoted apoptosis in mouse BC M49 cells [ 94 ]. Butler et al also showed that uropathogenic E. coli degraded c-MYC protein and attenuated MYC expression in tumor cells.…”
Section: Microbiota and Bladder Tumorigenesismentioning
confidence: 99%
“…The engineering plasticity of Salmonella enhances its efficacy in cancer therapy through improving safety, specificity, and delivery of anti-tumor therapeutic agents. It has been exploited for the delivery of cytotoxic agents such as cytolysin A, PE38, and diphtheria toxin, apoptosis-inducing proteins such as Fas ligand and TNF-related, apoptosis-inducing ligand (TRAIL), as well as apoptin and immunomodulatory cytokines, including IL-2, IL-12, IL-18, and IFN-γ [ 34 , 42 , 43 , 44 , 45 , 46 ]. Engineering plasticity enables the application of Salmonella in the expression of anti-cancer agents, “prodrugs,” or tumor-specific antigens at tumor sites.…”
Section: Why Is Salmonella the Best Option?mentioning
confidence: 99%